2020
DOI: 10.1080/01434632.2020.1829632
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation: bolstering positive attitudes towards endangered language varieties? Evidence from implicit attitudes

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 106 publications
2
15
0
Order By: Relevance
“…Neither of the two attitudinal studies reported above measured attitudes (explicit or implicit) towards Standard German and its vernaculars in relation to French, an additional standardised contact variety present in the region (Vari and Tamburelli 2020;Weber 2009). Thus, it remains unclear to what degree French might also carry prestige and perhaps even be a functional standard variety 2 for the vernaculars of the Deutschsprachige Gemeinschaft, with some studies reporting that it competes with Standard German over H(igh) domains in some parts of the region (Gramß 2008;Nelde and Darquennes 2002).…”
Section: Belgische Eifel/"deutschsprachige Gemeinschaft" In Belgiummentioning
confidence: 99%
See 4 more Smart Citations
“…Neither of the two attitudinal studies reported above measured attitudes (explicit or implicit) towards Standard German and its vernaculars in relation to French, an additional standardised contact variety present in the region (Vari and Tamburelli 2020;Weber 2009). Thus, it remains unclear to what degree French might also carry prestige and perhaps even be a functional standard variety 2 for the vernaculars of the Deutschsprachige Gemeinschaft, with some studies reporting that it competes with Standard German over H(igh) domains in some parts of the region (Gramß 2008;Nelde and Darquennes 2002).…”
Section: Belgische Eifel/"deutschsprachige Gemeinschaft" In Belgiummentioning
confidence: 99%
“…Besides the significant lack of quantitative studies on explicit attitudes, we are only aware of one study investigating implicit attitudes in the Deutschsprachige Gemeinschaft (Vari and Tamburelli 2020). Their method applied an Implicit Association Test based on Greenwald et al (1998).…”
Section: Belgische Eifel/"deutschsprachige Gemeinschaft" In Belgiummentioning
confidence: 99%
See 3 more Smart Citations